Visualizing pectin polymer-polymer entanglement produced by interfacial water movement - Pierce, Aidan; Wagner, Willi Linus (Carbohydrate polymers, 2020)
In this report, we investigated the physical conditions for creating pectin polymer-polymer (homopolymer) entanglement. The potential role of water movement in creating pectin entanglement was investigated by placing water droplets—equivalent to the water content of two gel phase films—between two glass phase films and compressing the films at variable probe velocities. Slow probe velocity (0.5 mm/sec) demonstrated no significant debonding. Corresponding videomicroscopy demonstrated an occasional water bridge, but no evidence of stranding or polymer entanglement. In contrast, fast probe velocity (5 mm/sec) resulted in 1) an increase in peak adhesion strength, 2) a progressive debonding curve, and 3) increased work of cohesion (p < .001). Corresponding videomicroscopy demonstrated pectin stranding and delamination between pectin films. Scanning electron microscopy images obtained during pectin debonding provided additional evidence of both stranding and delamination. We conclude that water movement can supply the motive force for the rapid chain entanglement between pectin films.